2005
DOI: 10.1111/j.1464-410x.2005.05504.x
|View full text |Cite
|
Sign up to set email alerts
|

The changing presentation of germ cell tumours of the testis between 1983 and 2002

Abstract: Authors from London looked at patients diagnosed with germ cell tumours of the testis who presented between 1983 and 2002. They found that there was an overall increase in the percentage of patients presenting with stage I seminoma, with a significant reduction in the size of the primary tumour. The authors do not feel that they can clarify the reason for these changes. There is a 20‐year follow‐up of patients who had tumours of the ureter and renal pelvis treated with resection and renal autotransplantation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
47
3
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 25 publications
9
47
3
5
Order By: Relevance
“…bP trend = 0.056 for SIR across the three calendar year periods. contrast to seminoma, nonseminoma may be less affected by screening bias because nonseminoma may be less indolent and thus less likely to be diagnosed incidentally (26). However, an accelerated diagnosis of indolent seminoma at AIDS onset would not account for the continuing excess that we observed during the 2 years after AIDS onset.…”
Section: Discussioncontrasting
confidence: 43%
“…bP trend = 0.056 for SIR across the three calendar year periods. contrast to seminoma, nonseminoma may be less affected by screening bias because nonseminoma may be less indolent and thus less likely to be diagnosed incidentally (26). However, an accelerated diagnosis of indolent seminoma at AIDS onset would not account for the continuing excess that we observed during the 2 years after AIDS onset.…”
Section: Discussioncontrasting
confidence: 43%
“…Almost one-third (31.71%) of patients were diagnosed at stage I, which is contradictory to the study of Powles et al who described that the patients with stage I disease were more compared to other diagnosed stages and this was due to improved education and awareness of germ cell tumours, resulting in earlier diagnosis. The incidence of testicular cancer at stage I in seminoma was 17% and in nonseminoma it was 11% in the present study, similar to the study of Powles et al in the UK who observed that nonseminomas developed from seminomas (20). The mean age at stage I was highest as compared to other stages (II and III) in the present study.…”
Section: Treatment For Different Types Of Testicular Cancersupporting
confidence: 81%
“…[7][8][9][10] However, the distribution of the stages in our series differed markedly from that in the developed world. In developed countries, stage 1 disease is the most common and also shows a consistent rise, 7,11,12 whereas in our study stages 3 and 4 were the most common. The mean interval between onset of symptoms and presentation to a health care facility was unduly long (5.2 months, range 1 -12 months).…”
Section: Discussionmentioning
confidence: 42%